Analysiss Added Value Of Wood Yam As A Raw Material For Cassava Chips In Karanganyar Regency (Case In Kub Wanita Tani Makmur) - Valentina, Oxy (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2022)
The agricultural sector in the perspective of agribusiness with its role in the national economy provides several things that show advantages that can be considered. These advantages include added value in agro-industry. The cassava chips business at KUB Wanita Tani Makmur is one of the businesses in Karanganyar Regency which is managed simply with the use of limited technology. This study aims to determine the profit, efficiency and added value of processing cassava into cassava chips in Karanganyar Regency. . The basic research method used is descriptive method. The location of the research was determined purposively, namely KUB Wanita Tani Makmur Karanganyar Regency on the grounds that the members of KUB Wanita Tani Makmur in processing cassava are different, namely soaking cassava that has been half-cooked. The type of data used is primary data and secondary data with observation, interview and recording techniques. The data analysis method used is business analysis to determine the magnitude of the efficiency gain and added value. The results showed that the profit received from the business of processing cassava into cassava chips in one production process for members of KUB Wanita Tani Makmur from raw cassava to cassava chips totaled Rp. 10,375.61. Meanwhile, in KUB Wanita Tani Makmur, the profit received from cassava chips until they are cooked (cassava chips) is Rp. 1,610,418.99. The business efficiency of processing raw cassava to -finished cassava chips in Karanganyar Regency for members of KUB Wanita Tani Makmur is 1.11. Meanwhile, the efficiency of processing cassava chips until they are cooked at KUB Wanita Tani Makmur is 1.68. Processing of raw cassava into -finished cassava chips carried out by members of KUB Wanita Tani Makmur gave a gross added value of Rp. 52,043.74, net added value of Rp. 50,558.25, value added per raw material of Rp. 979.55/kg and added value per raw material. labor amounting to Rp 3,097.84/JKO.